The role of management accounting in the construction of the new generation leadership in family firms: An Actor- Reality perspective - Leotta, Antonio; Rizza, Carmela; Ruggeri, Daniela (Proceedings of Pragmatic Constructivism, 2017)
Succession in family firms may determine the survival or the failure of the business itself. Management accounting literature has added little to this issue, mainly focusing on the process of succession and change (Songini et. al, 2013; Giovannoni et al., 2011). The present study deals with new management accounting (MA) practices that the junior generation may introduce during the process of succession. The aim of the study is to show that the introduction of new MA practices can contribute to construct the leadership profile of the junior generation. Drawing on the perspective of Actor-Reality Construction, we conducted a case study at a small-sized, family firm producing solar shading systems. We examined how the process of succession derives from the integration of four dimensions of reality: facts, possibilities, values and communication. Such an integration is facilitated by the introduction of a new accounting information system and cost report. The case evidence highlights that the construction of the new generation leadership may emerge as unintended consequence of the introduction of new MA practices. From the emergent perspective of Actor-Reality Construction, the paper investigates the role of new management accounting practices in the actor-world relation constructing the new generation leadership.